Artesunate, an Anti-Malaria Agent, Attenuates Experimental Osteoarthritis by Inhibiting Bone Resorption and CD31hiEmcnhi Vessel Formation in Subchondral Bone - Li, Yicheng; Mu, Wenbo; Xu, Boyong; Ren, Jiangdong; Wahafu, Tuerhongjiang; Wuermanbieke, Shalitanati; Ma, Hairong; Gao, Hongwei; Liu, Yang; Zhang, Keyuan; Amat, Abdusami; Cao, Li (Frontiers in Pharmacology, 2019)
Osteoarthritis (OA) is a highly prevalent and debilitating joint disease worldwide without interventions available to reverse its progression. Artesunate (ART), an anti-malaria agent, possesses diverse biological activities, including the inhibition of osteoclastogenesis and angiogenesis in various cells, but its role in subchondral bone during OA progression is not known. Here, we investigated the effects of ART on the pathogenesis of OA in anterior cruciate ligament transection (ACLT) mice models. We found that ART attenuated articular cartilage degeneration, defined by lowered histologic scoring of OA and retarded calcification of the cartilage zone. Moreover, ART improved the expression of lubricin and aggrecan and reduced the expression of collagen X (Col X) and matrix metalloproteinase-13 (MMP-13). In parallel, ART normalized abnormal subchondral bone remodeling, demonstrated by the restoration of bone volume fraction (BV/TV), trabecular pattern factor (Tb.pf) and subchondral bone plate thickness (SBP Th.) to a level comparable to that of the sham group. We found that ART exerted protective effects in part by suppressing osteoclastic bone resorption through regulating RANKL-OPG system, restoring coupled bone remodeling by indirectly inhibiting Smad2/3-dependent TGF-β signaling. Additionally, ART abrogated CD31hiEmcnhi vessel formation via downregulating the expression of vascular endothelial growth factor and angiogenin-1 in subchondral bone. In conclusion, ART attenuates ACLT-induced OA by inhibiting osteoclastic bone resorption and CD31hiEmcnhi vessel formation in subchondral bone, indicating that this may be a new therapeutic alternative for OA.